ACCOUNTING, TAX AND AUDIT SPECIFICS IN DEPRECIATION AND AMORTIZATION OF LONG-TERM ASSETS (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyses the conceptual differences between economic depreciation and accounting amortization of long-term assets, as well as the conflicts between International Financial Reporting Standards (IFRS) and the Tax Code of the Republic of Uzbekistan in recording these. Based on concrete quantitative evidence, the impact of these differences on enterprise working capital is demonstrated, and the introduction of new analytical accounts into the national chart of accounts is proposed to improve the audit review process.
Keywords: Long-term assets, economic depreciation, amortization charges, IFRS (IAS 16), Tax Code, temporary differences, deferred taxes, audit methodology, chart of accounts.